Adoptive transfer of donor B lymphocytes: a phase 1/2a study for patients after allogeneic stem cell transplantation. - Winkler, Julia; Tittlbach, Hannes; Schneider, Andrea; Vasova, Ingrid; Strobel, Julian; Herold, Susanne; Maas, Stefanie; Spriewald, Bernd; Repp, Roland; Kordelas, Lambros; Mach, Michael; Wolff, Daniel; et al. (Blood Advances, 2024)
Immune reconstitution after allogeneic hematopoietic stem cell transplantation (allo-HSCT) is slow and patients carry a high and prolonged risk of opportunistic infections. We hypothesized that the adoptive transfer of donor B cells can foster after HSCT immuno-reconstitution. Here, we report, to our knowledge, the results of a first-in-human phase 1/2a study aimed to evaluate the feasibility and safety of adoptively transferred donor B cells and to test their activity upon recall vaccination. Good manufactoring practice (GMP) B-cell products were generated from donor apheresis products using 2-step magnetic cell separation. Fifteen patients who had undergone allo-HSCT were enrolled and treated after taper of immunosuppression (median, day +148; range, 130-160). Patients received 4 different doses of B cells (0.5 × 106 to 4.0 × 106 B cells per kg body weight). To test the activity of infused donor memory B cells in vivo, patients were vaccinated with a pentavalent vaccine 7 days after B-cell transfer. We observed the mobilization of plasmablasts and an increase in serum titers against vaccine antigens, with a stronger response in patients receiving higher B-cell numbers. Analysis of immunoglobulin VH-sequences by next-generation sequencing revealed that plasmablasts responding to vaccination originated from memory B-cell clones from the donor. Donor B-cell transfer was safe, as no Epstein-Barr virus (EBV) reactivation was observed, and only low-grade graft-versus-host disease (GVHD) occurred in 4 out of 15 patients. This pilot trial may pave the way for further studies exploring the adoptive transfer of memory B cells to reduce the frequency of infections after allo-HSCT. This trial was registered at ClinicalTrial.gov as #NCT02007811.
EVALuna2:562572